2023
DOI: 10.1128/spectrum.04261-22
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Genetic Characteristics of Clinical Carbapenem-Resistant Pseudomonas aeruginosa Strains in Guangdong Province, China

Abstract: Carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a major concern in clinical settings worldwide, yet few genetic and epidemiological studies on CRPA strains have been performed in China. Here, we sequence and analyze the genomes of 416 P. aeruginosa strains from hospitals in China to elucidate the genetic, phenotypic, and transmission characteristics of CRPA strains and to identify the molecular signatures responsible for the observed increase in the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
3
2
Order By: Relevance
“…Carbapenem-resistant P. aeruginosa usually shows resistance to the vast majority of clinical antibiotics and even XDR due to the production of carbapenemase, high efflux pump expression, and deletion of outer membrane protein. In our study, most XDR-hvPA strains were carbapenemase producers, suggesting that the production of this enzyme is the main mechanism leading to their drug resistance, which is inconsistent with previous research [ 22 – 24 ]; this inconsistency can be attributed to all strains in this study being XDR and plasmids carrying multidrug resistance genes being obtained from outside. It is worth noting that among these carbapenemases in XDR-PA in our study, bla GES was the most prevalent, which is mainly detected in P. aeruginosa [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Carbapenem-resistant P. aeruginosa usually shows resistance to the vast majority of clinical antibiotics and even XDR due to the production of carbapenemase, high efflux pump expression, and deletion of outer membrane protein. In our study, most XDR-hvPA strains were carbapenemase producers, suggesting that the production of this enzyme is the main mechanism leading to their drug resistance, which is inconsistent with previous research [ 22 – 24 ]; this inconsistency can be attributed to all strains in this study being XDR and plasmids carrying multidrug resistance genes being obtained from outside. It is worth noting that among these carbapenemases in XDR-PA in our study, bla GES was the most prevalent, which is mainly detected in P. aeruginosa [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The predominant age group in our study was 31-40 years. Our data are in contrast with previously reported age groups such as 41-60 years from Pakistan [72], >60 years of age from China [12,79], 46-60 years from India [86] and 45-65 years from England [87]. It is evident from these reports that CRPA infections are frequently reported in old age group; however, its incidence among age groups 31-45 years and <20 years has been described in India and Oman [86,88].…”
Section: Discussioncontrasting
confidence: 99%
“…This variability might be attributed to lower sample size in such studies. On the other hand, global data showed that CRPA prevalence variations based on different geographic locations such as European and Mediterranean countries (ranging from 10.9% in Sweden to 70.5% in Poland) [20], China (89.4%) [12], Egypt (64.2%) [73], Turkey (20%) [74], India (33%) [75] and Nigeria (40%) [76]. Similarly, a multicenter study in 10 different countries reported 22% [77] and the SENTRY surveillance program 23.9% [78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations